Redesign Stadion Mini Universitas Sumatera Utara dengan Pendekatan Arsitektur Struktur sebagai Elemen Estetis - Wildan Prismana Dalimunthe; Mohammad Dolok Lubis (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
The University of North Sumatra Mini Stadium is a sports complex covering an area of 6.4 hectares. This facility is located on Jalan Almamater, Padang Bulan, Medan Baru, Medan City, North Sumatra. Various sports activities are facilitated in this area, including volleyball, basketball, tennis, table tennis, taekwondo, rock climbing, archery, and soccer, all of which are integral parts of the facilities and infrastructure available at the Mini Stadium. In addition to the main stadium, the University of North Sumatra Mini Stadium complex is equipped with various supporting buildings and fields. These facilities serve as a means for developing and channeling students’ interests and athletic talents, as well as a public space that can be utilized by the people of Medan City for sports activities. However, functionally, the University of North Sumatra Mini Stadium complex is considered suboptimal in effectively accommodating and supporting sports activities. The non-compliance of installations with applicable standards, as well as the condition of a number of facilities that no longer meet suitability criteria and tend to be neglected particularly the soccer field and its supporting facilities are the main problems at the University of North Sumatra Mini Stadium complex. Therefore, the redesign of the University of North Sumatra’s mini stadium, using a structural architecture approach as an aesthetic element, is expected to result in a building that is not only structurally sound but also aesthetically pleasing.